Gambaran Paru-paru pada Pemeriksaan Radiografi Thorax Pasien Covid-19 Terkonfirmasi di Ruang Perawatan ICU Covid-19 dan Non-ICU Covid-19 RSUD Raden Mattaher Jambi - Intan Fadilah; Chairunnisa; Hanina (Journal of Medical Studies, 2024)
ABSTRACT Background: The emergence of the Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in December 2019 caused the CoronaVirus Disease-2019 (Covid-19) pandemic, which is an acute disease that attacks mainly the respiratory system. Chest Radiography is considered capable of describing the condition of the lungs in Covid-19 patients. The purpose of this study was to see the description and location of pulmonary infiltrates on chest radiography examinations in confirmed Covid-19 patients. Methods: This study uses a descriptive research method with a retrospective approach that uses secondary data, namely data from the radiology work station computer. Results: The radiographic examination of the thorax was in the form of minimal infiltrates, infiltrates, and consolidation in the lungs, while the location of the infiltrates was found in bilateral perihilar, bilateral perihilar and paracardial lung, upper and middle lung fields, mid- and lower-pitched fields. lungs, the entire field of both lungs, especially the peripheral side. Conclusion: The most of the chest radiographic images of ICU and non-ICU patients were infiltrates. The location of the most infiltrates in ICU patients is throughout the fields of both lungs, especially the peripheral side, while non-ICU patients are in the middle and lower lungs. The gender of the majority of ICU patients are male, while the majority of non-ICU patients are female. The average age of ICU patients is 55 years, while the average age of non-ICU patients is 52 years. Keywords: Chest radiography, Covid-19, pneumonia ABSTRAK Latar belakang: Kemunculan virus corona Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) di bulan Desember 2019 menyebabkan pandemik CoronaVirus Disease-2019 (Covid-19), yaitu penyakit yang memiliki sifat akut menyerang terutama pada sistem pernapasan. Radiografi thorax dianggap mampu menggambarkan kondisi paru-paru pada pasien Covid-19. Tujuan penelitian ini adalah untuk melihat gambaran dan lokasi infiltrat paru di pemeriksaan radiografi thorax pada pasien Covid-19 terkonfirmasi. Metode: Penelitian ini menggunakan metode penelitian deskriptif dengan pendekatan retrospeksif yang menggunakan data sekunder, yaitu data dari komputer work station bagian radiologi. Hasil: Gambaran pemeriksaan radiografi thorax adalah berupa infiltrat minimal, infiltrat, dan konsolidasi di paru, sedangkan untuk lokasi infiltrat ditemukan pada perihiler bilateral paru, perihiler dan parakardial bilateral paru, lapangan atas dan tengah paru, lapangan tengah dan bawah paru, seluruh lapangan kedua paru terutama sisi perifer. Kesimpulan: Gambaran radiografi thorax terbanyak pasien ICU dan non-ICU berupa infiltrat. Lokasi infiltrat terbanyak pada pasien ICU adalah diseluruh lapangan kedua paru terutama sisi perifer sedangkan pasien non ICU adalah tengah dan bawah paru. Jenis kelamin mayoritas pasien ICU yaitu laki laki, sedangkan mayoritas pasien non ICU yaitu perempuan. Usia rata rata pasien ICU yaitu berusia 55 tahun sedangkan pasien non ICU rata rata usianya yaitu 52 tahun. Kata kunci: Radiografi thorax, Covid-19, pneumonia